ENGLISH PROPER NOUNS AND THEIR LINGUACULTURAL ASPECTS (Academicia Globe: Inderscience Research, 2021)
This article is devoted to investigate English proper nouns which contain culture-related information. They were divided into main groups: idiomatic expressions with the structure of knowledge related to religion, myths and legends, literature, geography, history and culture. They convey significant information about people’s way of life, religious principles, historical events, geographical places, etc. Theoretical part of the article is proved by numerous examples of English proper nouns which were chosen for linguo-cultural approach of investigation. The objectives of the research: English proper nouns with linguo-cultural content. The following methods of the research were used: descriptive method, comparative and cross-cultural analysis. Results obtained: linguocultural information in the semantics of English proper nouns with idiomatic expressions has been revealed and approved by numerous examples. Conclusion: the structures of religious, mythological, historical, literature-related, geographical and national-specific knowledge have been defined in the meaningful content of idioms.